Remediation experiment of Ecuadorian acid mine drainage: geochemical models of dissolved species and secondary minerals saturation - Delgado, J (2020)
Acid mine drainage is one of the main environmental hazards to ecosystems worldwide and it is directly related to mining activities. In Ecuador, such acidic-metallic waters are drained to rivers without treatment. In this research, we tested a laboratory combined (Ca-Mg) Dispersed Alkaline Substrate (DAS) system as an alternative to remediate acid drainage from the Zaruma-Portovelo gold mining site, at El Oro, Ecuador. The system worked at low and high flow hydraulic rates during a period of 8 months, without signs of saturation.. Analysis of physico-chemical parameters and water composition (ICP-OES, ICP-MS) demonstrated that treatment effectively increased water pH and promoted the retention of about 80% of Fe, Al, Mn and Cu. Under acid conditions As, Cr and Pb concentrations decreased with Fe and possible precipitation of jarosite and schwertmannite. However, the homogeneous depletion of Cr at pH above 6 could be related to ferrihydrite or directly with Cr (OH)(3) precipitation. After DAS-Ca, sulphate, phosphate and rare earth elements (REE) concentrations decreased to 1912, 0.85 and 0.07 mg/L respectively, while DAS-Mg contributed to form a complex model of minor carbonate and phosphate phases as main sink of REE. DAS-Mg also promoted the retention of most divalent metals at pH values over seven. Thus, this low cost treatment could avoid environmental pollution and international conflicts. Anyway, further investigations are needed to obtain higher Zn retention values.